Perencanaan Interaktif Pengelolaan Sampah Berbasis Keterlibatan Masyarakat di Kawasan Perkotaan Surabaya - Annisa Azzahra Putri; Puspaningtyas, Anggraeny; Hartono, Supri (Public Administration Dept, Faculty of Social and Political Science, 2026)
This study aims to analyze stakeholder involvement in interactive waste management planning in Surabaya City. The focus of this study is to see how stakeholders and the community are interactively involved in interactive waste management planning with Ackoff's theory which has six indicators: chaos formulation, goal planning, means planning, resource planning, implementation design, and control design. This study uses a qualitative approach with a descriptive type. The data sources used in this study are primary data obtained from interviews conducted with the Surabaya City Bappeda, the Surabaya City Environmental Agency, Pakal District, Sumber Rejo Village, Nginden Jangkungan Village, and Jambangan Village. As well as secondary data obtained from books, journals, and regulations relevant to the research topic. The data analysis technique uses 4 stages according to Miles and Huberman 2014, namely 1) Data Collection, 2) Data Condensation, 3) Data Presentation, and 4) Conclusion Drawing or Verification. The results of the study indicate that interactive planning in Surabaya City has demonstrated the involvement of various actors at each stage. However, this still does not fully reflect every indicator in interactive planning according to Ackoff. This is because decision-making, policy formulation, and programs are still dominated by the government and the Surabaya City Environmental Agency. Community involvement tends to be indirect and uneven among stakeholders at all planning stages. This research is expected to provide recommendations to local governments, particularly the Environmental Agency, to increase engagement by at least outlining the stakeholders involved in formulating strategic waste management plans for the next five years.